Pengaruh Modal, Luas Lahan dan Zis (Zakat, Infak, Sedekah) Terhadap Pendapatan Petani Cabai Merah (Studi Di Desa Sidodadi Ramunia Kecamatan Beringin Kabupaten Deli Serdang) - Pebrianti, Ririn; Indah Lestari Nasution, Annio; Aslami, Nuri (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
This research aims to determine the influence of capital, land area and Zis (Zakat, Infak, Sedekah) on the income of red chili farmers in Sidodadi Ramunia Village, Beringin District, Deli Serdang Regency. This research is descriptive quantitative research, the data collection method is a questionnaire. The subjects of this research focused on 102 red chili farmers by taking samples using the Saturated Sampling technique. The data used in this research is secondary data which was processed using the SPSS 22 application. Based on the results of hypothesis testing, it can be concluded that partially capital has a significant and positive effect on red chili farmers' income, partially land area has a significant and positive effect on farmers' income. red chilies and partially ZIS have a significant and positive effect on farmer income. Red chili pepper. Capital, land area and ZIS simultaneously have an influence on the income of red chili farmers in Sidodadi Ramunia Village, Kec. Banyan District. Deli Serdang. This means that capital, land area and zis have an influence on the income received by red chili farmers.Key Words: Religiosity, Budget Constraints, Social Media, Consumption Behavior